23rd Annual Conference of the German Crystallographic Society, March 16-19, 2015, Göttingen, Germany : abstracts. (De Gruyter, 2015)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> Zeitschrift für Kristallographie. Supplement Volume 35 presents the complete Abstracts of all contributions to the 23rd Annual Conference of the German Crystallographic Society in Göttingen (Germany) 2015.
Keywords: Earth sciences.; Geophysics.; Materials -- Texture -- Congresses.; Metals -- Texture -- Congresses.; Texture (Crystallography) -- Congresses.; elektronické knihy; electronic books